Grafični evfemizmi v računalniško posredovani komunikaciji - Michelizza, Mija; Vranjek Ošlak, Urška (Slavia Centralis, 2020)
Graphic euphemisms in computer mediated communication The paper presents the analysis of graphic euphemisms of selected swear words in Slovenian computer mediated communication (on Twitter and in online news comments) and identifies different ways in which CMC users disguise taboo words in order to avoid automatic detection and deletion of their tweets or comments. Most common graphic euphemism types are the substitution of a letter with a non-letter symbol and the insertion of a non-letter symbol. Doubled letters are common as well. The substitution of letters with visually similar symbols, other letters or letter combinations with similar pronunciation are less frequent. The analysis also shows that CMC users are very innovative; juxtaposition, puns and various word formation procedures are very common, even though their primary role is language play rather than taboo word encryption.